THE POWER OF BROCHURE: A MULTIMODAL DISCOURSE ANALYSIS ON CHILDREN EDUCATIVE TOY “HAFIZ AND HAFIZAH TALKING DOLL” - Siska Eka Syafitri (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
Brochure as a media in promoting a product has developed by the growing of technology in this multimedia era. The inovation in brochure in fact is needed to support a success marketing. The images and words which are showed in the brochure should be present in meaningful and creative ways. It will catch the interest and raise the curiosity of the customers. Seeing the situation, studying the popular product by the brochure delivered is very important. “Hafiz and Hafizah Talking Doll” is one of the popular product in this global era. It is a kind of educative toy that is contained of many features as its superiority . This product has caught many customer and we can find so many online brochures in the internet. Therefore, analyzing the brochure of “Hafiz and Hafizah Talking Doll” is very essential. Multimodal Discourse Analysis is applied in this research to get the understanding of the brochure.